A study on peroneus longus autograft for anterior cruciate ligament reconstruction - K., Kumar V.; K., Narayanan S.; B., Vishal R. (International Journal of Research in Medical Sciences, 2019)
Background: To compare the clinical outcome and donor site morbidity of ACL reconstruction with Peroneus longus tendon autografts in patients with isolated ACL injury. Methods: This was a prospective study that included patients who underwent ACL reconstruction using Peroneus longus tendon autograft. Results were assessed via physical examination. Donor site morbidity of the foot and ankle after tendon harvesting was assessed using Medical Research Council (MRC) grading of ankle and foot movements. Post-operative knee function was evaluated by the International Knee Documentation Committee (IKDC) scoring. Results: In this study sample of 25 patients, the ankle functions at the donor site are grossly preserved in almost all the patients, which was elucidated by grading the power of foot eversion. Post operatively knee function (IKDC scoring) were rated as normal in 92% (23 cases). Conclusions: Peroneus longus is an appropriate autograft source for ACL reconstruction in view of ease of harvest, adequate size, cosmetically appealing, considering excellent post-operative knee scores. And removing the Peroneus longus tendon has no effect on gait parameters and does not lead to instability of the ankle. So, it can be used as an autogenous graft in orthopaedic surgeries.